HR i møte med det nye arbeidslivet - Thon, Andreas N. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
This anthology is the second in a series of books from the Department of Management and Organization at Kristiania University College. HR in Today's Working Life builds on the book Leading People in Today's Working Life (2020). Through its 12 chapters, the book explores such HR- and management-related topics as: global uncertainty, unforeseeable change, crisis management, predictive analysis and scenario thinking, managerial development and management practices, health-oriented self-management, managerial recruitment, new forms of connection in working life, managers' legal maneuvering room, demographic development and diversity in working life, and the caregiver's role. The chapters have there starting point in various aspects of current working life. The authors discuss how changes in and around businesses have necessitated an evolved understanding of what influences organizations and people, a need for new HR practices, and new approaches to how managers should exercise their role. The book builds on central dimensions of HR and management as research fields: • Good management and a good working life in Norway are best developed through an understanding of the Norwegian context. • Good HR and managerial practice are based on solid insight into how an organisation's resource and capability needs are influenced by both internal factors and external changes. • Implicit in fostering a good working life is having a conscious relationship to the global factors and trends that are drivers of change that in turn affect organisations, work, people and managers. The book's 17 authors are forward-thinking Norwegian researchers and professionals in their fields. Each chapter explores themes, issues and concepts with the goal of offering new insights into research and practice in the Norwegian context. The authors contribute to research-based knowledge development in working life today through theoretical, conceptual and empirical studies. The book is therefore aimed at researchers and students, as well as specialists and managers with an interest in HR, organization and management. HR in Today's Working Life has been edited by Andreas N. Thon (senior lecturer in management, organisation and HR at Kristiania University College), Laura E. M. Traavik (associate professor in organization and management at Kristiania University College) and Kjetil A. Vedøy (lecturer at the Department of Management and Organisation, Kristiania University College).